Phenotypic differentiation in a resilient dung beetle species induced by forest conversion into cattle pastures - Soto, C. Soledad; Giombini, Mariano I.; Giménez Gómez, Victoria C.; Zurita, Gustavo A. (Evolutionary ecology, 2019)
Forest conversion into lands for different uses is a widespread practice in tropical and subtropical regions. Such anthropogenic disturbance drastically modifies environmental conditions and availability of resources for species (ecological niche). While many species usually disappear or become rare, other (resilient species) persist in the disturbed areas, being subject to new and often stressful conditions (ecological filters). The issue of whether human-driven habitat modifications induce phenotypic changes in resilient organisms at the intraspecific level has been poorly studied thus far. In this study, we used the neotropical dung beetle Canthon quinquemaculatus to test the hypothesis that the conversion of native forest into open cattle pastures can induce phenotypic differentiation in the functional morphology of resilient species. Sexual dimorphism and year of collection were simultaneously evaluated as potential sources of intraspecific variation in the measured morphological traits. We measured several functional traits related to thermal niche, burrowing capacity and food resource manipulation, including body size and shape and the size of the anterior leg and its constitutive parts. We found significant morphological differentiation between habitats (native forest vs. cattle pasture), sexes and years in terms of multi- and single-trait comparisons. Individuals from cattle pastures were smaller and less spherical (because of lower body thickness) compared to individuals from native forest. Males were larger with bigger anterior tibia and femur while females were more spherical. The phenotypic differences observed between individuals from native and converted habitats could be attributed to plasticity and/or contemporary (adaptive) evolution. From an ecological viewpoint, this study shows that habitat disturbance may affect morphological variation and functional diversity at the intraspecific level which may in turn influence ecosystem functions that dung beetles perform (i.e. dung burial).